2015
DOI: 10.1021/acsami.5b05649
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of N-Doped Graphene as Efficient Electrocatalyst for Oxygen Reduction Reaction

Abstract: A facile bottom-up method is reported here for the fabrication of N-doped graphene for oxygen reduction. It consists of a two-step calcination strategy and uses α-hydroxy acids (AHAs) as carbon source and melamine as nitrogen source. Three different AHAs, malic acid, tartaric acid, and citric acid, were chosen as the carbon sources. The prepared N-doped graphenes have a typical thin layered structure with a large specific surface area. It was found that the N content in the obtained N-doped graphenes varies fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 39 publications
(59 reference statements)
1
37
1
1
Order By: Relevance
“…The ratio of intensity of D/G bands (I D /I G ) can give a quantitative estimation of the degree of graphitization ,. The same I D /I G value (0.93) of N−C and MnCo 2 O 4 /N−C catalysts indicates a high degree of graphitization, which is beneficial for improvement of the electrical conductivity …”
Section: Resultsmentioning
confidence: 99%
“…The ratio of intensity of D/G bands (I D /I G ) can give a quantitative estimation of the degree of graphitization ,. The same I D /I G value (0.93) of N−C and MnCo 2 O 4 /N−C catalysts indicates a high degree of graphitization, which is beneficial for improvement of the electrical conductivity …”
Section: Resultsmentioning
confidence: 99%
“…Due to the lower adsorption energies of O 2 molecule (not shown here) on WGs under flat, 10% and 20% compression, only the WGs under 30%, 40% and 50% compression are considered in the following (presented as p-30, p-40 and p-50, and p represents pure). Previous studies have shown that N-doping of graphene is considered to be an effective method to enhance the ORR performance due to the charge redistribution among surrounding C atoms caused by the higher electro-negative of N atom than C atom [5,[40][41][42]. First, we have calculated the formation energy E f of the N-doped WG under 30%, 40% and 50% compression (presented as N-30, N-40 and N-50, respectively, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic voltammetry measurements were carried out in the potential range 0.2–−0.8 V vs. Ag/AgCl with a 10 mV s −1 scan rate . ORR polarization curves were acquired in 4‐electrode configuration by cathodically scanning the disk electrode from 0.2 V–−0.8 V with a fixed 5 mV s −1 scan rate and 2500 rpm rotation speed; the ring electrode was kept at a fixed 0.2 V potential.…”
Section: Methodsmentioning
confidence: 99%